Implikasi Yuridis Terhadap Privasi Akses Pornografi - Adinda Setyaning Utami (Faculty of Law, Universitas Airlangga, 2023)
Abstract People who consume pornographic content are more likely to support violence. Law No. 44 of 2008 concerning pornography has been regulated regarding prohibited actions, which are contained in Article 4 - Article 14 of the Pornography Law. Meanwhile, just watching for himself then his act will not be an offense, but if it begins with the activity of downloading pornographic files (and not for himself) then disseminating it is an offense in the provisions in Articles 5 and 6 of the Pornography Law and of course it can. convicted. Therefore, writing focuses on the basis of consideration that a person should not be convicted of accessing pornographic content and the implications that arise as a result of accessing pornographic content, because there are no specific rules that regulate not being allowed to access or watch content that contains pornography, but it is related to privacy rights, free with private life is the government's responsibility as well as to consider binding provisions as a preventive measure in criminal acts due to pornographic content. Keywords: ; Porn; Criminal Crime; Delict; Privacy, Cyberporn. Abstrak Orang-orang yang mengonsumsi konten pornografi memiliki sikap cenderung mendukung kekerasan. Undang-Undang No. 44 Tahun 2008 Tentang Pornografi telah diatur mengenai tindakan yang dilarang, yang terdapat dalam Pasal 4 – Pasal 14 UU Pornografi. Sedangkan, menonton saja untuk dirinya sendiri maka perbuatannya itu tidak akan menjadi delik, tetapi jika diawali dengan aktivitas mengunduh file porno (dan tidak untuk dirinya sendiri) kemudian menyebarluaskan itu sudah termasuk delik dalam ketentuan di Pasal 5 dan 6 Undang- Undang Pornografi dan tentu dapat dipidana. Oleh karena itu, penulisan menitikberatkan terhadap dasar pertimbangan tidak dipidananya seseorang mengakses konten pornografi dan implikasi yang muncul akibat mengakses konten pornografi, karena belum ada aturan khusus yang mengatur tentang tidak boleh mengakses atau menonton konten yang bermuatan pornografi, tetapi berkaitan dengan privacy rights, bebas dengan kehidupan pribadi adalah tanggung jawab pemerintah juga untuk memikirkan ketentuan yang mengikat sebagai upaya preventif dalam tindakan kriminal akibat konten pornografi. Kata kunci : Pornografi; Kejahatan Kriminal; Tindak Pidana; Rahasia; Kejahatan Siber Pornografi